PENGEMBANGAN SISTEM INTERPRETASI DATA UNTUK SISTEM TELEMETRI CURAH HUJAN - , FERDI FEBRIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this research is to create a program to interpret the data from a system, which is used to monitor measuring rainfall as early warning system for avalanche cold lava from Mount Merapi. This system contains a remote station (transducers, Counter Timer, Frequency converter, CPM FSK Modulator and Tx/Rx) and station controllers (Tx/Rx, FSK demodulator, and a personal computer equipped with a precipitation data processing program). Data processing that was developed in this study using a matlab software expected to be used in interpreting data on rainfall of telemonitoring of Mount Merapi. A pair of handy-transceiver is used as data transmission with frequency in the VHF wave Amateur Radio data (144,100 MHz). Rainfall data change 60 ml in 10 seconds delay time variation is shipped with sound 1,668 seconds to 0,158 seconds. This research is expected to provide valuable information for the development of telemonitoring system engineering, especially for engineers working in the field of telemonitoring systems and for the people who live around Mount Merapi